TEACHING VOCABULARY TO THE THIRD SEMESTER STUDENTS OF TBI FTIK IAIN PALU THROUGH DIALOGUE - Kuliahana, Ana (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2017)
This research aims at increasing of students’ vocabulary through dialogue. This is a Classroom Action Research implemented in cycling process covering planning, acting, observing and reflecting. The subject of this research was thirty students of TBI FTIK IAIN Palu. The data were obtained from observation checklist, questionnaire, field notes and test. They were analyzed qualitatively and quantitatively. Qualitative data dealt with teaching-learning process i.e. students’ participation in classroom activities. Quantitative data were gained from students’ achievement on tests. The findings of the research indicated that most students participated actively in classroom activities. The findings revealed that in meeting 6 there were twenty three students who achieved minimum criteria of achievement. It means that the criteria achieved were 76.66%. Classical achievement is based on the number of students who get the score at least the criteria of success (60). Both the classical and individual achievements have met the criteria of success. It can be concluded that the use of dialogue is effective to increase the students’ vocabulary.